2017
DOI: 10.1016/j.bmcl.2017.02.070
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic optimitzation of CCG-203971: Novel inhibitors of the Rho/MRTF/SRF transcriptional pathway as potential antifibrotic therapeutics for systemic scleroderma

Abstract: We recently reported the development of a novel inhibitor of Rho-mediated gene transcription (1, CCG-203971) that is efficacious in multiple animal models of acute fibrosis, including scleroderma, when given intraperitoneally. The modest in vivo potency and poor pharmacokinetics (PK) of this lead, however, make it unsuitable for long term efficacy studies. We therefore undertook a systematic medicinal chemistry effort to improve both the metabolic stability and the solubility of 1, resulting in the identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 18 publications
1
52
0
Order By: Relevance
“…To investigate the role of the MRTF/SRF pathway in the regulation of FGFR1 in hMSCs, we inhibited the pathway using CCG203971 [48,49] . Indeed, in both hMSCs and fibroblasts, inhibition of the MRTF/SRF pathway reduced FGFR1 expression by 59.6±7.0% (p<0,01) and 61.5±2.9% (p<0.01), respectively (Fig 5a, c).…”
Section: Actin-myosin and Mrtf/srf Pathway Regulate Fgfr1 Expressionmentioning
confidence: 99%
“…To investigate the role of the MRTF/SRF pathway in the regulation of FGFR1 in hMSCs, we inhibited the pathway using CCG203971 [48,49] . Indeed, in both hMSCs and fibroblasts, inhibition of the MRTF/SRF pathway reduced FGFR1 expression by 59.6±7.0% (p<0,01) and 61.5±2.9% (p<0.01), respectively (Fig 5a, c).…”
Section: Actin-myosin and Mrtf/srf Pathway Regulate Fgfr1 Expressionmentioning
confidence: 99%
“…CCG-222740, previously reported by Hutchings et al (30), was a kind gift of Scott Larsen at the Vahltechich Medicinal Chemistry Core (Ann Arbor, MI). CCG-222740 was dissolved in DMSO in 10 mM aliquots and stored at -20 °C.…”
Section: Inhibitorsmentioning
confidence: 99%
“…Through structure-activity relationship optimization of CCG-203971, we recently reported the analog CCG-222740 with increased potency of MRTF-pathway inhibition in primary human dermal fibroblasts (30). Additionally, CCG-222740 demonstrated a greater inhibitory effect on MRTF/SRF target genes (ACTA2 and CTGF) and lesser cytotoxicity than CCG-203971 in a preclinical model of fibrosis (31).…”
Section: Introductionmentioning
confidence: 99%
“…Vemurafenib (#S1267), Y-27632 (#S1049), fasudil (#S1573), and dasatinib (#S1021) were purchased from Sellekchem, Houston, TX, USA. CCG-222740 15 was synthesized in the lab of Dr. Scott Larsen at the University of Michigan. All compounds were diluted in DMSO to a stock concentration of 10 mM.…”
Section: Compounds and Antibodiesmentioning
confidence: 99%
“…Silencing of MRTF or SRF, a transcription factor by which MRTF modulates gene expression, prevents melanoma metastasis 24 . Previously, we have developed a series of MRTF-pathway inhibitors including CCG-203971 and CCG-222740 1, 10,15 and demonstrated that CCG-203971 prevents melanoma metastasis, induces G1 cell cycle arrest, and reduces growth of melanoma cells 10 . YAP1 has been shown to promote BRAFi/MEKi resistance in melanoma through suppression of apoptosis via BCL-xL and BIM dysgulation 7, 14, 17, 22 ; accumulation of YAP1 protein and enrichment of a YAP1 gene signature has been documented in about 40% of clinical melanoma samples from patients who relapsed on MAPK inhibitor therapies 14 .…”
mentioning
confidence: 99%